A research on electronic business: comparison of electronic business models - Erdilek, Melisa (My University, 2002)
The most important impact of Internet and Web-based technologies have been recently observed in business life and in commercial transactions. Developments in computer and communication technologies started to dominate the business environment and changed the business rules. Relatively, speed between the business processes has increased while the importance of distances decreased and the value of information increased. The flow of information has eventuallly affected the way of doing businesses. On account of this, new business models have emerged. Traditional business models have been no longer valid in new business environment. Among the new business models, agora, aggregation, value chains, alliances and distributive networks have arisen. In these business webs, portals-isps, search engines and online auctions started to set the rules. In this thesis, the primary aim is to evaluate the e-business models by analyzing the reasons and the process of transformation of business to electronic business. In conclusion, within the research findings ,business webs are compared with each other, both International and Turkish wide. The basic requirements and the primary issues, that companies will take into consideration while conducting a new business in online platform, are underlined.

Internet ve Web- tabanlı teknolojiler son zamanlarda en fazla iş hayatı ve ticari işlemlerde etkisini göstermeye başladı. Bilgisayar ve komunikasyon teknolojilerindeki gelişmeler iş dünyasında etkin olmaya başladı ve buna paralel olarak iş kuralları da değişim gösterdi. İş süreçleri arasındaki hız arttı, mesafelerin önemi azalarak değer bilgi ile yaratılmaya başlandı. Aynı zamanda bilgi akışı işin yapılma şeklini etkiledi.Bu gelişmeler ışığında yeni iş modelleri ortaya çıktı. Geleneksel iş modelleri iş dünyasındaki geçerliliğini yitirdi . Yeni modellerden pazar yeri, bütünleştiriciler, değer zinciri, ittifak ve dağıtım networkleri önem kazandı. Bu iş modelleri çerçevesinde ise internet servis sağlayıcı -portallar, arama motorları ve sanal açık arttırmalar iş kurallarını belirlemeye başladı. Bu tezdeki amaç, dönüşümün nedenleri ve süreç incelenerek elektronik iş modellerinin analiz edilip değerlendirilmesidir. Nihai olarak,araştırma bulguları ışığında,uluslararası ve Türk iş modelleri birbiriyle kıyaslanarak incelendi.Şirketlerin elektronik ortama geçerkenki karşılaşabileceği süreçler , temel ihtiyaçlar ve birincil konuların altı çizildi.
Keywords: Bilgisayar programlaması; Bilgisayar sistemlerinde veri; Elektronik, İşletmeler’de; Genel Konular; İnternet, İşletmeler’de; Veri dosyaları ve tabanları